Microparticles from β-thalassaemia/HbE patients induce endothelial cell dysfunction - Kheansaard, Wasinee (Sci Rep, 2018)
Thromboembolic complication occurs frequently in β-thalassaemia/HbE patients, particularly in splenectomised patients. Endothelial cells play an important role in thrombosis. There is strong evidence of endothelial cell activation and dysfunction in β-thalassaemia. Microparticles (MPs) are associated with thrombosis and endothelial cell dysfunction in many diseases including β-thalassaemia. However, the effect of thalassaemic-MPs on endothelial cells mediating thrombus formation has not been elucidated. In this study, the effects of circulating MPs from β-thalassaemia/HbE patients on endothelial cell functions were investigated. The results showed that MPs directly induce tissue factor, interleukin (IL)-6, IL-8, intracellular adhesion molecule-1, vascular cell adhesion molecule-1 and E-selectin expression in human umbilical vein endothelial cells (HUVECs). Notably, the levels of these endothelial cell activation markers were significantly increased in HUVECs treated with MPs obtained from splenectomised β-thalassaemia/HbE patients when compared to MPs from non-splenectomised patients or normal subjects. The increased endothelial cell activation ultimately lead to increased monocyte-endothelial cell adhesion. THP-1 and HUVECs adhesion induced by MPs from normal subjects, non-splenectomised and splenectomised patients increased to 2.0 ± 0.4, 2.3 ± 0.4 and 3.8 ± 0.4 fold, respectively when compared to untreated cells. This finding suggests that MPs play an important role on thrombosis and vascular dysfunction in β-thalassaemia/HbE disease, especially in splenectomised cases.